Flexor Tendon Tenosynovitis in a Child Following Missed Thorn Prick Injury: A Case Report - Ghanghurde, Bipin A.; Habbu, Rohan; Avasthi, Bhupendra S. (Indian Journal of Plastic Surgery, 2025)
Plant thorn synovitis is a frequently missed and neglected injury. We report a delayed case of suspected thorn injury to the left middle finger in a 5-year-old child, which was treated with thorn removal and complete flexor synovectomy to achieve good results. Proper history, clinical examination, and correlated radiological findings can help in the diagnosis. Patients may seek late treatment due to persistent swelling and pain. Antibiotic may be given; however, in a delayed case, its role is debatable. Thorn removal and complete tenosynovectomy offers complete recovery.
Keywords: thorn prick injury; child; tenosynovitis